1995
DOI: 10.1002/j.2161-0045.1995.tb00524.x
|View full text |Cite
|
Sign up to set email alerts
|

A Values‐Based Approach to Facilitating Career Transitions

Abstract: This article outlines a values-based approach to facilitating career transitions. Values provide standards of behavior. People who are unable to engage in work that they deem important violate their standards of behavior and are likely to be dissatisfied with their jobs. Moreover, workers whose values are at variance with those of their supervisors are likely to have differing views of the relative importance of various aspects of the job. If a worker emphasizes aspects of the job that he or she views as impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…(p. 186) There are many reasons that voluntary midlife career changes occur. Occupational dissatisfaction (D. Brown, 1995;Donohue, 2007), a lack of challenge (Vander Zanden, 2000), lack of career-related identity (Dacey & Travers, 2004), stress and anxiety related to job insecurity (Donohue, 2007;Tivendell & Bourbonnais, 2000), workplace bullying (Donohue, 2007), and conflicts between work and other life roles (D. Brown, 1995) are some of the reasons cited for voluntary midlife career change.…”
Section: September 2011 • Volume 59mentioning
confidence: 99%
See 1 more Smart Citation
“…(p. 186) There are many reasons that voluntary midlife career changes occur. Occupational dissatisfaction (D. Brown, 1995;Donohue, 2007), a lack of challenge (Vander Zanden, 2000), lack of career-related identity (Dacey & Travers, 2004), stress and anxiety related to job insecurity (Donohue, 2007;Tivendell & Bourbonnais, 2000), workplace bullying (Donohue, 2007), and conflicts between work and other life roles (D. Brown, 1995) are some of the reasons cited for voluntary midlife career change.…”
Section: September 2011 • Volume 59mentioning
confidence: 99%
“…Precontemplators may present as discouraged (Prochaska et al, 1992), yet may not recognize the underlying reason as occupational dissatisfaction, which Bejian and Salomone (1995), D. Brown (1995), and Jepsen and Sheu (2003) asserted is a major reason that many individuals change careers in midlife.…”
Section: Precontemplation (Ttm)/disengagement (Lsls)mentioning
confidence: 99%
“…A great deal of work has been conducted to establish the existence and assess the impact of the value system on human functioning (Feather, 1990; Kilby, 1993; Kluckhohn, 1951; Rokeach, 1973; Schwartz & Bilsky, 1987) and particularly work behavior (Brown, 1995, 1996; Brown & Crace, 1996; Johnson, 2000, 2001a, 2001b, 2002; Mortimer & Lorence, 1979; Super, 1957, 1990, 1992, 1995) and to affirm that human development is partly defined in terms of value system development (Kluckhohn, 1951; Rokeach, 1973). This literature suggests that values and behavior mutually influence one another, yet little work has been conducted to determine how the value system develops over time.…”
mentioning
confidence: 99%
“…Perhaps these contradictions are a result of competing professional value systems (Brown 1995) that invoke different attitudes and goals. Reybold (2005) found that a core epistemology of the professorate defines professional meaningfulness in terms of motivating and disrupting forces.…”
Section: Discussionmentioning
confidence: 98%